Utilization of Digital Applications, Time Management, and Employee Skills Development to Improve Employee Performance Moonails - AryaPutra, Rendy An; Nuvriasari, Audita (Asian Journal of Community Services, 2024)
The internship program is conducted at Moonails Studio in Nail Art, focusing on training employees in skills and implementing an effective time management system. The main objective of this program is to improve efficiency and effectiveness in time management, as well as to improve the skills and ability of employees to improve work productivity within the company. The results of these services include significant improvements in employee soft skill skills, as demonstrated by an in-depth understanding of digital applications. Overall, this internship program is expected to bring positive benefits to the employee and company, improve operational efficiency, and quality of work, and create a comfortable and conducive working environment.